2020
DOI: 10.1590/s0100-83582020380100018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissimilarity in Conyza sumatrensis Revealed by Simple Sequence Repeat (SSR) Markers

Abstract: In view of the rapid evolution of Conyza sumatrensis populations resistant to glyphosate, it is necessary to understand the genetic diversity aimed to improve strategies for managing this weed. We investigated the genetic dissimilarity among 15 biotypes of C. sumatrensis from different geographic regions using microsatellite loci. The biotypes, were cultivated in a greenhouse to obtain vegetal material for DNA extraction. Nineteen microsatellite markers (SSR), were developed for C. sumatrensis biotypes. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The invasive potential and rapid range expansion of C. sumatrensis have been attributed to its persistent fecundity and high germination rate (Hao et al 2009); its production of a large number of small, wind-dispersed seeds, ranging up to more than 200,000 seeds per plant (Sansom et al 2013); and its high resistance to diseases, herbivory, and herbicides (Santos et al 2014a). Santos et al (2014bSantos et al ( , 2015 reported differential sensitivity to herbicides according to the stage of development of the plants, while Schneider et al (2020) reported the overexpression of genes in the resistant biotype treated with glyphosate. Differential sensitivity to herbicides according to growth stage was also reported in C. canadensis and C. sumatrensis populations by Travlos and Chachalis (2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The invasive potential and rapid range expansion of C. sumatrensis have been attributed to its persistent fecundity and high germination rate (Hao et al 2009); its production of a large number of small, wind-dispersed seeds, ranging up to more than 200,000 seeds per plant (Sansom et al 2013); and its high resistance to diseases, herbivory, and herbicides (Santos et al 2014a). Santos et al (2014bSantos et al ( , 2015 reported differential sensitivity to herbicides according to the stage of development of the plants, while Schneider et al (2020) reported the overexpression of genes in the resistant biotype treated with glyphosate. Differential sensitivity to herbicides according to growth stage was also reported in C. canadensis and C. sumatrensis populations by Travlos and Chachalis (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the economic importance of C. sumatrensis, few studies have particularly addressed the traits of this weed species. Only some reproductive (Hao et al 2009) and morphological (Sansom et al 2013) features, the occurrence of biotypes resistant to herbicides (Santos et al 2014a(Santos et al , 2014b(Santos et al , 2015, the impact of invasions on the soil microbiome (Rasool et al 2016), and genetic diversity within and among different biotypes (Marochio et al 2017;Schneider et al 2020) have been reported so far. Genetic diversity analysis of weed populations has practical importance, such as in predicting population response to biological or chemical control (Ward et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation